Artificial intelligence as a catalyst for systemic sport ecology - Ugo Arbieu; Laís Carneiro; Sonia Tieo; Franck Courchamp (Journal of Applied Sports Management, 2025)
Artificial intelligence (AI) is reshaping both sport management and environmental science, yet these developments have largely evolved in parallel. AI can serve not merely as a technical tool but also as a catalyst for systemic sport ecology, a field that integrates sport, digital innovation and environmental sustainability. Advances in discriminative, generative and agentic AI enable the synthesis of complex ecological and sport-related data, improving monitoring, forecasting, resource efficiency, policy design, and decision-making across scales. In doing so, AI offers a pathway beyond fragmented sustainability interventions and can support holistic approaches to the interconnected crises of climate change, pollution, and biodiversity loss. However, the catalytic potential of AI depends on responsible implementation, equitable access to data, and attention to environmental costs. In short, AI can drive systemic transformations by enhancing the collection and integration of social-ecological data, fostering governance innovation and operational sustainability within the sport sector.
Keywords: artificial intelligence; digital innovation; environmental sustainability; sport management; sport ecology